Adhesive film suitable for packaging Mini / Micro LED display panel

By using the adhesive film structure made of light-thermal double-solid composite glue, the problems of poor bottom fillability and complex process in the packaging of the Mini/Micro LED display panel are solved, and efficient and reliable packaging effect is achieved.

CN222684545UActive Publication Date: 2025-03-28GUANGZHOU SILICON CORE NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202421417561.7
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-03-28
Estimated Expiration
2034-06-20

AI Technical Summary

Technical Problem

During the preparation and use of traditional Mini/Micro LED display panel packaging film, there are problems such as poor underfillability, complex process and low production efficiency, and it is difficult to pass the trust test.

Method used

The adhesive film structure is made of light-thermal double-solid composite glue, including the upper release film, the functional adhesive layer, the wetting layer and the lower release film, and the semi-cured adhesive layer is formed by UV curing to improve the wetting property and the bottom filling effect of the adhesive film.

Benefits of technology

It achieves good wetting properties and chip bottom filling effect of Mini/Micro LED substrates, simplifies the process flow, improves production efficiency, and achieves high-reliability packaging through room temperature pressing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222684545U_ABST
    Figure CN222684545U_ABST
Patent Text Reader

Abstract

According to the adhesive film suitable for packaging the Mini / Micro LED display panel, through the semi-cured film made of the photo-thermal dual-curing composite glue, the wetting layer is formed by epoxy resin which does not participate in ultraviolet light curing in the adhesive film structure, the wettability of a film material to a substrate is improved, the filling effect of the film material to a cavity in the bottom of a chip is also improved, and the packaging quality of the chip is improved. The adhesive film is special in structure, easy to prepare and use and good in wettability to the Mini / Micro LED substrate, a chip can be embedded into the adhesive layer easily, the chip bottom filling effect is better, reliability is high, and cost is low. The problems that in the traditional adhesive film packaging process, permeability needs to be improved through a high-temperature softening adhesive layer, chip embedding is assisted, chip underfilling is carried out in advance, and reliability testing is difficult to pass are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of chip packaging, and specifically relates to an adhesive film suitable for chip packaging, in particular to an adhesive film suitable for Mini / Micro LED display panel packaging. Background Art

[0002] In the field of Mini / Micro LED high-definition display applications, the pixel pitch of the display panel is getting smaller and smaller, which also leads to an exponential increase in the number of light-emitting chips per unit area. The traditional packaging glue molding packaging is limited by the low efficiency of the solution and poor integrity, and it is increasingly difficult to meet the requirements. The film packaging has good integrity and simple process, which is bound to become the pursuit of future packaging processes. As a chip packaging film, it must first have bottom filling properties. At present, most of the films that can meet the bottom filling properties are more demanding in preparation conditions, and the packaging process is more cumbersome. The main reason is that a separate flow layer must be reserved, or an additional bottom filling glue must be used in the packaging process for chip bottom filling pre-treatment, that is, at least two different materials are required to make a multi-layer film structure. In addition to posing huge challenges to the thickness uniformity and preparation process of each layer, the packaging process is also increased, which directly affects production efficiency.

[0003] The black bottom film described in patent CN114373844A needs to be softened and flowed at high temperature to play the role of bottom filling, which places high requirements on the molding equipment. In addition, the encapsulation film also needs to wrap the chip without dead angles, which requires the film to have good wettability to the chip in the early stage of encapsulation. Therefore, a film that has both optical properties, simple preparation, easy use, and can achieve chip bottom filling and good wettability at the same time is of great significance to the film encapsulation process. Utility Model Content

[0004] The utility model aims to provide a film structure with special structure, simple use, good wettability to Mini / Micro LED substrates, easy chip embedding in the adhesive layer, better chip bottom filling effect and high reliability, so as to solve the problems of traditional film packaging process, such as the need to soften the adhesive layer at high temperature to improve permeability, assist chip embedding, pre-chip bottom filling and difficulty in passing reliability testing.

[0005] This application adopts the following technical solutions:

[0006] A film suitable for encapsulating Mini / Micro LED display panels, the film structure includes an upper release film, a lower release film and a composite adhesive layer disposed between the two; the composite adhesive layer is a semi-cured adhesive layer formed by UV curing of a light-heat dual-solid composite adhesive, the composite adhesive layer includes a film layer support composed of a cross-linked polymer and solid powder formed by a UV resin component after UV curing, and an epoxy resin component infiltrated and interspersed in the film layer support in the form of a fluid. Therefore, the light-heat dual-solid composite adhesive at least includes a UV resin and a photoinitiator, solid powder, epoxy resin and epoxy curing agent.

[0007] Preferably, the thickness of the composite adhesive layer is 90 to 250 μm, and the thickness of the composite adhesive layer used for encapsulation should be controlled at 100%-200% of the chip height. It should be understood that the purpose of encapsulation is first to provide all-round protection for the chip to ensure the long-term stability of the chip, secondly to ensure the appropriate optical effect, and finally to consider cost-effectiveness and aesthetics. Further preferably, the thickness of the composite adhesive layer is 160% of the chip height. Studies have found that in the process of UV curing to form a semi-cured composite adhesive layer, the thickness of the wet adhesive layer will be reduced by 0.5 to 2% on the original basis, and the thicker the adhesive film, the greater the impact. Therefore, the thickness of the wet adhesive layer can be appropriately increased according to the required thickness of the composite adhesive layer.

[0008] Research has found that there is no obvious boundary between the aforementioned film support and the epoxy resin component in the form of fluid, but the liquid uniformly infiltrating the surface of the middle composite adhesive layer is conducive to filling the bottom of the chip. For the convenience of explanation, we take the upper and lower surfaces of the film support as the ideal interface and divide the middle composite adhesive layer into a functional adhesive layer B and a wetting layer C. Therefore, the adhesive film structure in the utility model includes: an upper release film layer A, a functional adhesive layer B, a wetting layer C, and a lower release film layer D, such as Figure 1 shown.

[0009] The upper and lower release film layers A and D mainly play a protective role. The lower release film layer D is used as a base material for carrying glue during roll coating, while the upper release film layer A can prevent the glue from directly contacting the roller during the roll coating process, thereby reducing pollution. In addition, it should be understood that the upper and lower release film layers can be any one including but not limited to ordinary transparent PET release film, matte release film, frosted release film and other release films with special surface textures.

[0010] Preferably, the upper release film A has a release force of 80 to 120 g and a thickness of 75 to 100 μm.

[0011] Preferably, the lower release film D has a release force of 1 to 5 g and a thickness of 30 to 60 μm.

[0012] It should be understood that the adhesive film suitable for Mini / Micro LED display panel encapsulation described in the utility model will not retain any release film material after the final encapsulation is completed, which can further avoid affecting the long-term reliability of the display screen due to performance differences between different materials between the encapsulation layers.

[0013] The functional adhesive layer B is a semi-cured adhesive layer obtained directly from a wet adhesive layer obtained by coating a light-heat dual-curing composite adhesive and then curing it with ultraviolet light.

[0014] It should be understood that after the light-curing of the light-heat dual-curing composite glue, the main structures involved in the semi-cured glue layer are: B1 is the unreacted epoxy resin curing system glue, B2 is the cross-linked polymer formed after the UV resin is cured, and B3 is a solid mixture composed of various powders such as light diffuser, silicon micropowder and carbon black powder. After UV curing, in the structure of the semi-cured glue layer, B1, B2 and B3 are evenly distributed, and the cross-linked polymer B2 and solid particles B3 together form a "sponge"-like bracket structure, while B1 is infiltrated in the gaps therein, such as Figure 2 Among them, B1, B2 and B3 are only theoretical structures conceived for the convenience of explanation.

[0015] The wetting layer C is a liquid flow layer indirectly formed after the segmented curing process of the photothermal dual-solid composite glue, mainly composed of an epoxy system that does not participate in UV curing. It should be understood that after the wet glue layer prepared by the photothermal dual-solid composite glue is cured by UV light, the cross-linked polymer obtained by the UV resin reaction and the solid powder jointly form a solid support of the glue layer and the uncured liquid epoxy system to form a solid-liquid coexistence system, and finally a small amount of flowing epoxy liquid "escapes" on the surface of the functional glue layer B to indirectly form a wetting layer C with a uniform thickness. The study found that the thickness of the wetting layer C of the adhesive film made by the same photothermal dual-solid composite glue is almost stable and does not change due to the thickness of the film. This means that the wetting layer B is only physically infiltrated on the surface of the functional glue layer B, that is, when the proportions of the components of the photothermal dual-solid composite glue are uniform, the thickness of the wetting layer C on the surface of the functional glue layer B remains unchanged. After the release film is torn off, it can be monitored that the wetting thickness of a single surface is generally 1~10μm.

[0016] On the other hand, a film suitable for Mini / Micro LED display panel encapsulation is made from a photothermal dual-solid composite glue, which includes at least UV resin and photoinitiator, solid powder, active diluent, colorant, epoxy resin and epoxy curing agent.

[0017] Preferably, the UV resin is a modified polyurethane acrylate containing both carbon-carbon double bonds and hydroxyl groups, with an average molecular weight of 1500 and a viscosity of 15000 to 35000 mPa·s (25° C.).

[0018] It should be understood that the application of photothermal dual-solid composite glue in the field of Mini / Micro LED display panel packaging needs to ensure that it can eventually pass product reliability tests such as high and low temperature storage, hot and cold shock, high temperature and high humidity, and even high-pressure cooking. Therefore, in addition to ensuring that the adhesive layer formed by the semi-penetrating network polymer after UV curing can have a stable intermediate state, the photothermal dual-solid composite glue layer must also ensure that the various polymer components can be completely cross-linked in the final thermal curing reaction, and there is no phase separation behavior that reduces the reliability of the material. The study found that the adhesive film prepared by the photothermal dual-solid composite glue containing the above-mentioned modified polyurethane acrylate has better product reliability after being encapsulated and applied to Mini / Micro LED display panels.

[0019] Preferably, the photoinitiator is a free radical photoinitiator.

[0020] Preferably, the solid powder includes silicon powder, light diffuser and fumed silica.

[0021] Preferably, the viscosity of the reactive diluent is 30-100 mPa·s (25° C.).

[0022] Preferably, the use of a reactive diluent avoids the introduction of a solvent and is also beneficial for improving the uniformity of the components after high-density mixing, which plays a key role in ink color consistency and reliability.

[0023] Preferably, the colorant is a carbon black agent. Further preferably, the particle size of the carbon black is 0.1 to 10 μm, and the carbon black is prepared with bisphenol A epoxy resin by three-roll milling and ultrasonic treatment in advance to form a solvent-free carbon black slurry with a carbon black content of 20%. The amount of carbon black added will directly affect the light transmittance of the film, and is also directly related to the color contrast of the display screen after packaging and the light extraction efficiency of the RGB chip. It should be understood that in order to ensure the highest light transmittance, carbon black may not be added.

[0024] Preferably, the epoxy resin has a viscosity of 12000-15000 mPa·s (25° C.) and an epoxy equivalent of 160-200.

[0025] Preferably, the epoxy curing agent includes one or more of anhydride curing agents, hydrazide curing agents, imidazole curing agents and dicyandiamide curing agents.

[0026] It should be understood that as an adhesive film for Mini / Micro LED display panel encapsulation, the selection of epoxy curing agent should be considered from multiple angles such as transparency, chromaticity and curing performance, which will directly affect the light transmittance of the film and the final curing performance of the encapsulation adhesive layer. Different from anhydride curing agents, hydrazide curing agents not only have good transparency and low shrinkage and high TG curing properties, but also have good curing latency, thereby extending the storage period of the film.

[0027] Preferably, the mass ratio of UV resin to epoxy resin in the light-heat dual-solid composite glue needs to be controlled within W UV树脂 :W 混合环氧树脂 =1:5~20. More preferably, W UV树脂 :W 混合环氧树脂 =1:10, the obtained film product has moderate hardness and toughness, which is conducive to storage and transportation, and does not affect the use effect of the film.

[0028] The study found that when the proportion of UV resin is too low, after ultraviolet light, the degree of cross-linking inside the adhesive layer is extremely low, the bracket structure is extremely loose, and the resulting adhesive layer is soft and rotten and cannot be formed into a film; when the proportion of UV resin is too high, after ultraviolet light, the degree of reaction cross-linking is too high, and the density of the adhesive film is high. Although the surface of the adhesive layer still retains a certain wetting effect, the chip cannot be easily pressed and embedded in the adhesive layer, and may even be easily squeezed and fallen off, which cannot meet basic packaging requirements.

[0029] In a third aspect, the present application also provides a method for preparing an adhesive film for Mini / Micro LED display panel encapsulation, comprising the following steps:

[0030] S1 First, weigh the UV resin, solid powder, active diluent, colorant, and epoxy resin into a sealed container, and disperse them for 2 hours under vacuum using a dual planetary power mixer to obtain a uniformly mixed glue solution, which can be used only after returning to room temperature. Then, weigh the photoinitiator and epoxy curing agent into the glue solution, connect the circulating coolant outside the container, and disperse for 1 hour under vacuum to finally obtain the light-heat dual-solid composite glue. After discharging, store it away from light for later use;

[0031] S2: According to the required size of the package, pour the light-heat dual-solid composite glue obtained in step S1 on the left end of the lower release film layer D and cover it with the upper release film layer A, then place the coating preparation device on the left side of the glue and above the upper release film layer A (that is, the coating preparation device does not directly contact the glue throughout the process), adjust the slit of the coating preparation device, and control the thickness of the wet glue layer to 160% of the chip height. Finally, on the automatic coating machine, scrape the liquid glue between the upper release film layer A and the lower release film layer D from left to right to form a wet glue layer of specified thickness, and combine it with the upper release film layer A and the lower release film layer D to form a wet glue film, such as Figure 3As shown (a-film preparation device; b-vacuum adsorption plate);

[0032] S3: The wet adhesive film obtained in step S2 is placed in an ultraviolet light curing machine for ultraviolet light curing to obtain a semi-cured adhesive film. The area 5 mm away from the edge of the adhesive film is cut to obtain an adhesive film with uniform thickness suitable for Mini / Micro LED direct display screen packaging.

[0033] Preferably, in step S1, each component needs to be sheared at a high speed of 1800 rpm in a container under a vacuum environment. In addition to ensuring uniform mixing of the components and reducing the moisture content of the materials, it can also prevent active groups such as carbon-carbon double bonds (C=C) from being oxidized, thereby preventing the composite glue from yellowing.

[0034] Preferably, in step S2, the film sheet obtained by coating with two layers of release films is composed of: upper release film layer A / unphotofixed wet glue layer / lower release film layer D. The coating process is a calender coating process, and the film-making method using solvent-free glue can meet the requirements of non-contact film-making process, thereby avoiding glue pollution, and reducing subsequent processes such as volatile solvents, thereby improving efficiency and reducing pollution.

[0035] Preferably, in step S3, the UV curing conditions are: mercury lamp power is 1 KW, peak wave is 365 nm, mesh belt speed is 1.5 m / min, duration is 5 s, and both the front and back sides are irradiated once each.

[0036] In a fourth aspect, the present application also provides an application of an adhesive film suitable for Mini / Micro LED display panel packaging in Mini / Micro LED display panel packaging.

[0037] The packaging method of the film is as follows:

[0038] Cut the film into a size that matches the display panel to be packaged and tear off the lower release film layer D. Use a rubber roller to roughly roll the film onto the dry and clean display panel to be packaged, and then place the display panel with the film facing down in a vacuum flatbed laminator. After the equipment is started, it must be vacuumed for 60 to 120 seconds. After reaching the vacuum state, press at room temperature, and set the pressing time to 120 to 180 seconds. Set the pressure to 4 to 10 kg. After pressing, confirm that there are no bubbles and transfer to a 150°C oven for 2 hours of post-curing. After completion, take it out and tear off the upper release film layer A. The schematic diagram of the appearance of a single pixel of a display panel is as follows Figure 4 As shown, the pressing process is as follows Figure 5 shown.

[0039] Among them, after the adhesive film is attached to the Mini / Micro LED display panel, the epoxy resin components and solid particles in fluid form will infiltrate and fill the gap at the bottom of the Mini / Micro LED chip, and after subsequent thermal curing, a solid packaging layer will be formed as a whole to encapsulate the Mini / Micro LED display panel.

[0040] In patent CN115632002A, the adhesive film and the substrate need to be vacuum pressed at 90-110°C, and then placed in a 145-155°C oven for post-curing for 3-5 hours. In patent CN114373844A, when using the roller pressing process for pressing, the temperature of the hot roller is selected to be 100-200°C; when using the flat plate pressure transfer process for pressing, the vacuum pressing temperature is selected to be 70-180°C, and after the initial lamination is completed, it is placed in a 120-160°C oven for post-curing for 5 hours. It is worth noting that, different from the above schemes, the biggest difference of the utility model is that due to the presence of the wetting layer C in the adhesive film structure, the pressing process can be carried out at room temperature, reducing the heating step. It should be understood that the heating step in the pressing process is to improve the flow permeability of the adhesive film by heating and melting, so as to achieve the purpose of filling the gap at the bottom of the chip, and the wetting layer with its own wetting function in the adhesive film structure of the utility model can be directly realized, which not only improves the operational safety, but also saves energy.

[0041] Compared with the prior art, the utility model has the following advantages:

[0042] (1) The adhesive film used for encapsulating Mini / Micro LED display panels in the utility model has a composite adhesive layer that performs encapsulation by directly applying a solvent-free light-heat dual-solid composite adhesive once and then curing it with UV light, thereby avoiding the problem of uneven thickness and inconsistent ink color caused by multiple coatings;

[0043] (2) The adhesive film structure used for encapsulating Mini / Micro LED display panels in the utility model is a semi-cured film made of a light-heat dual-solid composite glue. The presence of a wetting layer in the structure improves the wettability of the film material to the substrate and also improves the filling effect of the film material on the cavity at the bottom of the chip, greatly improving the encapsulation efficiency;

[0044] (3) The adhesive film structure used in the utility model for encapsulating Mini / Micro LED display panels can meet the chip bottom filling requirements without the need to soften the adhesive layer at high temperature during the lamination process, thus saving energy and ensuring safe operation;

[0045] (4) The adhesive film structure used for encapsulating Mini / Micro LED display panels in the utility model can adjust the softness of the adhesive layer by controlling the mass ratio of UV resin and epoxy resin, so that the RGB chip can be easily embedded during the encapsulation process. In addition to ensuring that the chip will not fall off and fail due to extrusion force, it can also ensure that the chip is tightly wrapped by the encapsulation adhesive layer to improve reliability, thereby extending the service life of the display product;

[0046] (5) The internal polymer of the packaging material of the utility model is densely cross-linked, which can further improve the packaging reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.

[0048] Figure 1 It is a schematic diagram of the structure of the adhesive film in this application;

[0049] Figure 2 is a schematic diagram of the interior of the adhesive film in this application;

[0050] Figure 3 It is a schematic diagram of the preparation process of the adhesive film in this application;

[0051] Figure 4 It is a schematic diagram of the appearance of a unit pixel of the display panel in this application;

[0052] Figure 5 It is a schematic diagram of the pressing process in this application;

[0053] Figure 6 This is a comparative demonstration diagram of the effect of chip underfill in this application;

[0054] Figure 7 is the wettability test result of the adhesive layer in this application;

[0055] Figure 8 It is the observation result of the microscopic appearance of the sample surface in this application;

[0056] Fig. 9 It is a schematic diagram of the packaging effect of different film thicknesses in this application. DETAILED DESCRIPTION

[0057] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict.

[0058] A film suitable for encapsulating Mini / Micro LED display panels, wherein the encapsulating adhesive layer is made of a light-thermal dual-solid composite glue, and the light-thermal dual-solid composite glue comprises the following raw materials in parts by weight:

[0059] Table 1: Raw materials in parts by weight of Examples 1-3:

[0060]

[0061] The specific production steps are as follows:

[0062] S1. Add the weighed mixed epoxy resin, UV resin, epoxy reactive diluent, toughening resin, solid powder and colorant into a sealed container, and disperse them for 2 hours under vacuum using a dual planetary power mixer to obtain a uniformly mixed glue solution, which can be used only after returning to room temperature. Then, add the weighed photoinitiator and epoxy curing agent into the glue solution, connect the circulating coolant outside the container, and disperse for 1 hour under vacuum to finally obtain a light-heat dual-solid composite glue. After discharging, store it away from light for later use.

[0063] S2, lay the lower release film layer D (release surface facing upward) on the platform of the automatic coating machine, then pour the glue obtained in step S1 on the lower release film layer D as needed, and then cover the upper release film layer A (release surface facing downward) on the adhesive layer, adjust the slit of the coating preparation device, control the thickness of the wet adhesive layer to 160% of the chip height, start the automatic coating machine to scrape once, and you can get a wet adhesive film; the release force of the upper release film A is 100g, and the thickness is 100μm. The lower release film D is a PET release film with a release force of 3g and a thickness of 50μm.

[0064] S3, placing the wet adhesive film obtained in step S2 in an ultraviolet light curing machine for ultraviolet light exposure (mercury lamp power of 1 kW, peak of 365 nm, mesh belt speed of 1.5 m / min, duration of 5 s), once on each side, to finally obtain a semi-cured adhesive film with a composite adhesive layer thickness of about 160% of the chip height.

[0065] The packaging method of the film is as follows:

[0066] Cut the film into a size that matches the display panel to be packaged and tear off the lower release film layer D. Use a rubber roller to roughly roll the film onto the dry and clean display panel to be packaged, and then place the display panel with the film facing down in a vacuum flatbed laminator. After the equipment is started, it needs to be vacuumed for 60 to 120 seconds. After reaching the vacuum state, keep pressing at room temperature, and the pressing time is set to 120 to 180 seconds; the pressure is set to 4 to 10 KG. After pressing, confirm that there are no bubbles and transfer it to a 150°C oven for 2 hours of post-curing. After completion, take it out and tear off the upper release film layer A.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 2 is that the slit of the coating film preparation device is adjusted to finally obtain a semi-cured adhesive film with a composite adhesive layer thickness of about 100% of the chip height.

[0069] Comparative Example

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the prepared light-heat dual-solid composite adhesive has a mass ratio of: W UV树脂 :W 混合环氧树脂 =1:21 (i.e. the corresponding UV resin is 4.76 parts). After UV irradiation, the degree of cross-linking reaction is extremely low, the structure is extremely loose, the adhesive layer is soft and rotten, and it cannot be formed into a film.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 1 is that the prepared light-heat dual-solid composite adhesive has a mass ratio of: W UV树脂 :W 混合环氧树脂 =1:4 (i.e. the corresponding UV resin is 25 parts).

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 1 is that the glue used for film making does not contain UV resin and photoinitiator. The obtained glue cannot be photocured, and remains in a glue state after being irradiated with ultraviolet light, and cannot be fixed into a film for use.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that no epoxy resin and epoxy curing agent are added. Since the proportion of filler is too high, the glue cannot be prepared successfully.

[0078] Comparative Example 5

[0079] The difference between this comparative example and Example 2 is that the slit of the coating film preparation device is adjusted to finally obtain a semi-cured adhesive film with a composite adhesive layer thickness of about 80% of the chip height.

[0080] Comparative Example 6

[0081] The difference between this comparative example and Example 2 is that the slit of the coating film preparation device is adjusted to finally obtain a semi-cured adhesive film with a composite adhesive layer thickness of about 60% of the chip height.

[0082] Comparative Example 7

[0083] The difference between this comparative example and Example 2 is that the slit of the coating film preparation device is adjusted to finally obtain a semi-cured adhesive film with a composite adhesive layer thickness of about 300% of the chip height.

[0084] The test characterization method is as follows:

[0085] 1. Texture of adhesive layer

[0086] Use the finger pressure method to make a simple judgment. Remove the lower release film layer D from the film and place it on a flat surface for testing. For soft textures, use your fingers to press to determine whether the adhesive layer will be damaged or whether it will stick to your hands and fall off; for hard textures, use your fingernails to press to determine whether the adhesive layer has white marks or breaks.

[0087] 2. Wettability of adhesive layer

[0088] First, cut the prepared adhesive film (rectangle with a side length of 3 to 5 cm) and dry weighing paper (rectangle with a side length of 1 to 2 cm), place the adhesive film on a flat surface (lower release film layer D facing upwards), tear off the lower release film layer D, use tweezers to clamp the cut weighing paper on the adhesive layer and let it soak naturally until stable, observe the degree of wetting of the weighing paper and take photos to record. Use the same cold air source to blow the attached and stable weighing paper for 10 seconds to determine whether the weighing paper can be blown away.

[0089] 3. Glue layer bottom filling test

[0090] After encapsulating the film on the Mini / Micro LED display panel, use the cross-section sawing method to confirm whether there is a cavity under the chip, such as Figure 6 As shown (1-glue layer after encapsulation curing; 2-RGB chip; 3-chip bonding bumps; 4-unfilled gap between chip and substrate; 5-filled area between chip and substrate; 6-substrate).

[0091] 4. Appearance and structure of adhesive layer

[0092] Before using an electron microscope to observe the film structure, the samples need to be grouped and subjected to the following pretreatment operations:

[0093] (1) Use acetone and ethyl acetate solvents to completely dissolve most of the organic matter in the film, thereby exposing the internal solid powder distribution. The specific operation process is as follows: After tearing off the release film layer D, soak the film in acetone solvent for 2 hours and ethyl acetate solvent for 2 hours, then take it out and bake it in a 60℃ oven for 8 hours, and observe the surface appearance. (It should be noted that the pretreatment process needs to be handled with care throughout the process to avoid loosening the solid powder and destroying the original support appearance of the film layer);

[0094] (2) The wetting layer C that "escaped" from the bracket to the surface of the functional adhesive layer B is adsorbed cleanly by physical adsorption, so as to facilitate the observation of the actual surface appearance of the functional adhesive layer B. After the release film layer D is torn off, the film is gently attached to the surface of the adhesive layer with dry weighing paper, and the weighing paper is gently torn off after it is moistened. This operation is repeated 3 to 5 times until the weighing paper is no longer soaked, and the surface appearance is observed.

[0095] The test results of the adhesive layer texture, wettability and bottom filling are shown in Table 2 and Figure 7 As shown;

[0096] Table 2: Results of adhesive layer texture, wettability and bottom filling test

[0097]

[0098] By comparing the wettability results of each glue layer in Examples 1 to 3 and Comparative Example 2, it is also reflected from the side that there is a wetting layer with B1 as the main body on the surface of the glue layer. The existence of the wetting layer first ensures the wettability of the substrate surface and the filling of the bottom of the chip. The bracket structure formed by B2 and B3 after UV curing plays a key role in the pressing and packaging process, which is mainly closely related to the hardness of the bracket structure. When the proportion of UV resin is too low, after UV irradiation, the degree of crosslinking inside the glue layer is extremely low, the bracket structure is extremely loose, and the prepared glue layer is soft and rotten, and cannot be formed into a film; when the proportion of UV resin is too high, after UV irradiation, the degree of reaction crosslinking is too high, and the density of the glue film is high. Although the surface of the glue layer still retains a certain wetting effect and there is also a bracket structure, the RGB chip cannot be smoothly embedded in the glue layer during the pressing process due to the toughness of the bracket structure. Finally, the glue film cannot form an embedding effect on the chip and a cavity appears, and it is even easy to cause the chip to fall off and fail due to extrusion, which cannot meet the basic packaging requirements. When the ratio of UV resin to epoxy resin is appropriate, that is, WUV resin: W mixed epoxy resin = 1:5-20, the film texture is soft and appropriate. During the lamination process, the bracket structure formed can meet the normal embedding of the RGB chip, thereby ensuring that no cavity is formed around the chip. Figure 6 As shown, the adhesive layer can form a tight wrap around the chip; when the chip is embedded, there is a tendency to squeeze the adhesive film, making it easier for the wetting layer to be filled into the cavity area between the chip and the substrate.

[0099] The surface microstructure of the sample from Example 2 was observed, and the results are shown in Table 3 and Figure 8 As shown:

[0100] Table 3: Film microstructure test results

[0101]

[0102] The film samples of Examples 2, 4 and Comparative Examples 5, 6, and 7 were taken to compare the effects of different film thicknesses on the encapsulation effect. The results are shown in Tables 4 and Fig. 9 As shown:

[0103] Table 4: Comparison results of packaging with different film thicknesses:

[0104]

[0105] According to the purpose of film packaging, a film with moderate thickness can not only meet the all-round protection of RGB chips, but also ensure the optical effect required when the RGB chips are displayed. Controlling the thickness moderately can also ensure aesthetics and cost-effectiveness. It is worth noting that after the film is embedded in the chip, due to the increase in the inherent volume of the chip, the final encapsulation layer that is higher than the PCB substrate will actually be higher than the original thickness of the film. When the film thickness is thin, the volume increase at the chip embedding position first appears as a convex state, that is, the increased volume mainly tends to fill the area above the film chip. When the film thickness itself is thin, under the same pressing pressure, it is easy to show a convexity above the corresponding chip, thereby affecting the surface flatness of the entire display screen. It should be understood that the film described in the utility model is composed of a film layer support composed of a cross-linked polymer formed by UV resin components after UV curing and solid powder, and an epoxy resin component infiltrated and interspersed in the film layer support in the form of a fluid. To a certain extent, the film layer support is relatively fixed. Although the hardness and softness of the film layer can be adjusted by formula ratio, the film cannot be completely naturally leveled under the condition of fixed pressing pressure. After many verifications, in order to make the display screen have a flat surface, the most suitable thickness of the composite adhesive layer used for packaging should be controlled to 120~180% of the chip height.

[0106] The main features of the adhesive film structure of the utility model are concentrated as follows:

[0107] (1) The utility model is suitable for the adhesive film used for encapsulation of Mini / Micro LED display panels, wherein the composite adhesive layer that plays the role of wetting the bottom fill and encapsulation is directly formed by a single coating of a solvent-free light-thermal dual-solid composite glue and then UV curing, thereby avoiding the problem of uneven thickness and inconsistent ink color caused by multiple coatings.

[0108] (2) In the present invention, the ratio of light-curing resin to heat-curing resin (i.e. W UV树脂 :W 混合环氧树脂 ) Adjust the hardness of the functional adhesive layer B to ensure that the adhesive film can be easily embedded in the chip and maintain good mechanical properties.

[0109] (3) The structure of the composite film layer in the utility model that plays key functions such as wetting and chip bottom filling during the attachment process to the Mini / Micro LED substrate is actually a wetting layer C mainly composed of uncured epoxy resin infiltrated on the surface of the functional adhesive layer B.

[0110] (4) During the use of the adhesive film of the utility model, the wetting layer C can provide a more efficient bonding and wetting effect, and the adhesive film itself does not need to be softened by high temperature, but can smoothly penetrate into the cavity under the chip by relying on the flow dynamics of the wetting layer itself.

[0111] (5) The adhesive film of the utility model is formed by a semi-permeable network polymer produced by ultraviolet light curing to form a functional adhesive layer B and a wetting layer C in a semi-cured film state, which can be completely cross-linked after the final thermal curing, thereby improving the packaging reliability.

[0112] Therefore, the utility model relates to providing a film structure with a special structure, simple preparation, simple use, good wettability to Mini / Micro LED substrates, easy chip embedding in the adhesive layer, better chip bottom filling effect and high reliability, so as to solve the problems of traditional film packaging process, such as the need to soften the adhesive layer at high temperature to improve permeability, assist chip embedding, pre-chip bottom filling and difficulty in passing reliability testing.

[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. An adhesive film suitable for Mini / Micro LED display panel encapsulation, characterized in that: It includes an upper release film, a lower release film and a composite adhesive layer arranged therebetween; The composite adhesive layer includes a membrane layer support and a wetting layer in the form of a fluid that is infiltrated and interspersed in the membrane layer support.

2. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1, characterized in that: The thickness of the composite adhesive layer is 90-250 μm.

3. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1 or 2, characterized in that: The composite adhesive layer is a semi-cured adhesive layer formed by coating a light-heat dual-curing composite adhesive into a wet adhesive layer and then curing it with UV.

4. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 3, characterized in that: The thickness of the wet glue layer is 90-255 μm.

5. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1, characterized in that: The wetting layer is epoxy resin.

6. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 5, characterized in that: The epoxy resin includes an alicyclic epoxy resin.

7. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1, characterized in that: The membrane layer support is formed by UV resin composition after UV curing.

8. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1, characterized in that: The release force of the upper release film is 80-120 g, and the thickness is 75-100 μm.

9. The adhesive film for Mini / Micro LED display panel encapsulation according to claim 1, characterized in that: The lower release film has a release force of 1 to 5 g and a thickness of 30 to 60 μm.

10. The adhesive film for Mini / Micro LED display panel encapsulation according to any one of claims 1, 8 and 9, characterized in that: The upper release film and the lower release film are made of any one of a transparent PET release film, a matte release film and a frosted release film.

Citation Information

Cited By

  • Micro LED display module packaging adhesive film and preparation method thereof

    CN121780079A